Effectiveness and Safety of High‐Dose Biologics in Juvenile Idiopathic Arthritis in the Childhood Arthritis and Rheumatology Research Alliance. Issue 11 (31st July 2022) - Correll, Colleen K.; Shrader, Peter; Dennos, Anne; Phillips, Thomas; Shiff, Natalie J.; Verstegen, Ruud H. J.; Beukelman, Timothy
Abstract : Objective: To describe high‐dose biologic use when treating juvenile idiopathic arthritis (JIA). Methods: Patients with JIA enrolled in the Childhood Arthritis and Rheumatology Research Alliance Registry and treated with a biologic after enrollment were eligible. We described the frequency of high‐dose biologic use and characteristics of patients receiving high‐dose biologics. We used regression modeling to compare 6‐month outcomes (using disease activity measures) between those who increased their biologic from standard to high dose (high‐dose group) to those who initiated and remained on standard dosing (no‐change group), and to those who switched biologic agents (biologic‐switch group). We also compared serious adverse events (SAEs) between groups. Results: A total of 5, 352 patients with JIA were treated with biologics following enrollment; 1, 080 (20%) had ever received a high‐dose biologic. There were no significant differences in outcomes between the high‐dose group and the biologic‐switch group; both improved disease activity measures, including the clinical Juvenile Arthritis Disease Activity Score 10 (–3.53 and –3.95, respectively; P = 0.68). Although the SAE rates in the high‐dose group and the biologic‐switch group were numerically higher than the no‐change group, the event rates were similar, and neither rate was significantly higher than in the no‐change group (unadjusted incident rate ratio 2.5 [95% confidence interval (95% CI) 0.7–8.5] and 1.8 [95% CI 0.7–4.6], respectively). Conclusion: Dosing escalation appears to be a reasonable choice to improve disease control, but large, prospective, randomized studies evaluating specific biologic agents are needed.